"Etude de l’application des hydroxydes doubles lamellaires dans le domaine catalytique" - إكرام, الأطرش; كوثر, عياشي عمر; سناء, بشر (University of El-Oued, 2022)
In this study we present bibliographical studies on lamellar double hydroxides and their applications in the catalytic field. LDHs consist of Mg(OH)2 brucite type sheets. In which part of the divalent metal cations has been replaced by trivalent ions, giving positively charged sheets. This charge is balanced by introducing anions into the interleaf region. The mixed oxides formed by calcinations at high temperatures make these materials porous and present a large specific surface. These materials are of interest in certain heterogeneous catalytic reactions. Bibliographic studies have shown that these catalysts have a high selectivity towards hydrogenation reactions. نقدم في هذه الدراسة دراسة ببليوغرافية عن الهيدروكسيدات الرقائقية المزدوجة وتطبيقاتها في المجال التحفيزي. تتكون HDLs من صفائح من نوع البروسيت Mg(OH)2، حيث تم استبدال جزء من الكاتيونات المعدنية ثنائية التكافؤ بأيونات ثلاثية التكافؤ، مما يعطي صفائح موجبة الشحنة، تتم موازنة هذه الشحنة عن طريق إدخال الأنيونات في المنطقة البينية. الأكاسيد المختلطة المتكونة من عمليات التكليس في درجات حرارة عالية تجعل هذه المواد مسامية وتقدم سطحًا محددًا كبيرًا. هذه المواد ذات أهمية في بعض التفاعلات التحفيزية الغير متجانسة، أظهرت الدراسات الببليوغرافية أن هذه المحفزات لديها انتقائية عالية تجاه تفاعلات الهدرجة.
مذكرة ماستر تخصص هندسة طرائق
Keywords: LDHs, catalyst, mixed oxides, selectivity, hydrogenation.; هيدروكسيدات الصفائح المزدوجة ، محفز ، أكاسيد مختلطة ، انتقائية ، هدرجة.